Reading Comprehension Performance Among Impulsive and Reflective English Learners: Examining the Influence of Three Reading Methods - Marjon Moiinvaziri (National Research University Higher School of Economics, 2024)
Background: Exploring the impact of various reading methods - such as oral reading, silent reading, and the relatively understudied subvocalization method - on the comprehension abilities of language learners with different cognitive styles, including reflective and impulsive learners, can contribute significantly to understanding how different reading techniques enhance comprehension across diverse cognitive styles.   Purpose: To investigate the role of three reading methods, including oral, silent, and subvocalization, on the comprehension performance of a group of English as a Foreign Language (EFL) learners, considering the cognitive styles of impulsivity and reflectivity. Method: In this study, 60 female students studying in first-grade senior high school were selected based on purposive sampling. Employing a counterbalanced quasi-experimental design with three treatments, the research investigated how different reading methods influenced the impulsive and reflective learners' reading performance. The impulsivity and reflectivity of the participants were determined by Eysenck's Impulsiveness Questionnaire (I.7). Results: The results revealed that all participants, both reflective and impulsive, demonstrated better comprehension performance with oral and subvocalization methods compared to silent reading. The oral and subvocalization methods had a similar effect on their performance. Reflective learners outperformed impulsive learners across all three methods, showing significantly higher performance. Additionally, most participants expressed a preference for oral reading over the other two methods.  Conclusion: The outcomes suggest the importance of teachers' increased flexibility in utilizing diverse reading methods and considering learners' diverse characteristics, including their cognitive style, in classroom instruction